1972
DOI: 10.1073/pnas.69.3.721
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement by Interferon of the Specific Cytotoxicity of Sensitized Lymphocytes

Abstract: Mouse interferon preparations enhanced the specific cytotoxicity of sensitized lymphocytes for allogeneic target tumor cells. The factor responsible for the enhancement of cytotoxicity could not be dissociated from the antiviral activity of interferon by standard physicochemical means. Thus, in addition to its well-known antiviral activity, and its effect on cell division, interferon also appears to enhance a specialized cellular function. It is suggested that a common mechanism of action underlies these seemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
89
1

Year Published

1973
1973
2005
2005

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 271 publications
(90 citation statements)
references
References 18 publications
0
89
1
Order By: Relevance
“…In vitro experiments showed that IFN-a induces cyclin-dependent kinase inhibitors involved in G1/G0 arrest (Sangfelt et al, 1999). Interferon-a may also exert its antitumour effect indirectly via the immune system since IFN-a is known to augment T-cell cytotoxicity (Lindahl et al, 1972;Trinchieri et al, 1978). Recently, we reported that the modulation of tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) receptor-mediated cytotoxic pathway could partially contribute to the anti-HCC effect of IFN-a/5-FU combination therapy (Yamamoto et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments showed that IFN-a induces cyclin-dependent kinase inhibitors involved in G1/G0 arrest (Sangfelt et al, 1999). Interferon-a may also exert its antitumour effect indirectly via the immune system since IFN-a is known to augment T-cell cytotoxicity (Lindahl et al, 1972;Trinchieri et al, 1978). Recently, we reported that the modulation of tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) receptor-mediated cytotoxic pathway could partially contribute to the anti-HCC effect of IFN-a/5-FU combination therapy (Yamamoto et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Control preparations consisted of the medium of uninoculated cell cultures or tissues of uninoculated animals. Preparation and semipurification of murine interferon have been described (15 (L 1210 and EL4 cells were maintained by serial passage in ascitic form in DBA/2 and C57B1/6 mice, respectively). The mice were bled 1 week after the last injection.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the well-known antiviral action (1), interferon preparations also exert various biologic effects on cells (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). The nature of some of these effects suggested the possibility that interferon treatment might be associated with modifications of the cell surface.…”
mentioning
confidence: 99%
“…In addition to interferon's well-known antiviral action, preparations of it have been reported to exert multiple effects on cells [i.e., inhibition of the multiplication of bormal and tumor cells in culture (2)(3)(4)(5), inhibition of the growth of a variety of transplantable tumors in mice (6)(7)(8), modulation of the synthesis and release of specific cellular products (9)(10)(11)(12)(13)(14)(15)(16), modification of the cell surface (17)(18)(19)(20)(21), and modulation of both the humoral (22)(23)(24)(25)(26)(27) and cell-mediated immune responses (28)(29)(30)(31)(32)(33)(34)]. Although experimental results support the hypothesis that the antiviral action of interferon is only one manifestation of its effect on cells (35)(36)(37), it is important to emphasize that these experiments were undertaken using preparations in which interferon protein constituted at most only 1% of the total protein content.…”
mentioning
confidence: 99%